Abnormal Lipid Profiles in Nontraumatic Osteonecrosis of the Femoral Head: A Comparison with Osteoarthritis Using Propensity Score Matching. (6th April 2022) - Baek, Seung-Hoon; Kim, Kwang-Hwan; Lee, Won Kee; Hong, Wonki; Won, Heejae; Kim, Shin-Yoon
Abstract : Background: Abnormal lipid metabolism may play an important role in the development of nontraumatic osteonecrosis of the femoral head (ON). By comparing lipid biomarkers in patients with ON and osteoarthritis (OA) after propensity score matching, we sought to reveal (1) common lipid biomarkers that are abnormal in ON regardless of the etiology and (2) specific lipid biomarkers associated with ON according to the etiology. Methods: Among 2, 268 patients who underwent primary THA, 1, 021 patients were eligible for this study. According to the Association Research Circulation Osseous criteria, ON was classified as either idiopathic (n = 230), alcohol-associated (n = 293), or glucocorticoid-associated ON (n = 132). Most common cause of OA was hip dysplasia in 106 patients (47%). We investigated patient lipid profiles by assessing total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglycerides (TGs), apolipoprotein (Apo) A1 and B, lipoprotein (a) levels and ApoB/A1 ratio. Since age and body mass index affect the lipid profile, we performed propensity score matching to select 304 patients for final analysis and compared lipid profiles between the ON and OA groups. We also compared biomarkers between the ON subgroups and the OA group. Results: Overall, the ON group showed lower HDL-C (p < 0.001), higher TGs (p = 0.001) levels and higher ApoB/A1 ratio (p = 0.003). Idiopathic ON patients demonstrated lower HDL-C (p = 0.032), higher TGs (p = 0.016), ApoB (p = 0.024) levels and ApoB/A1 ratio (p = 0.008). The alcohol-associated ON subgroup showed lower HDL-C (p < 0.001), higher TGs (p = 0.010) levels and ApoB/A1 ratio (p = 0.030). Finally, the steroid-associated ON subgroup demonstrated lower HDL-C (p = 0.003), higher TGs (p = 0.039), lower TC (p = 0.022), LDL-C (p = 0.021), and ApoA1 (p = 0.004) levels. Conclusions: Higher TGs and lower HDL-C levels were associated with nontraumatic ON regardless of the etiology. Additionally, idiopathic ON was associated with higher ApoB levels and ApoB/A1 ratio. Alcohol-associated ON was related to higher ApoB/A1 ratio, and steroid-associated ON paired with decreased TC, LDL-C, and ApoA1 levels. Our findings may support future efforts for prevention and management of nontraumatic ON. Level of Evidence: Diagnostic Level III.